Diversity beyond demographics: Environmental worldviews of forestry and natural resource undergraduate students. Issue 8 (11th August 2022) - Cruz, Sativa; Batavia, Chelsea; Arismendi, Ivan; Spalding, Ana; Nelson, Michael Paul
Abstract: In US academic institutions, efforts often concentrate on enhancing the recruitment of students from underrepresented groups, focusing on gender and/or race. However, little attention has been paid to nondemographic forms of diversity, such as environmental worldviews (i.e., differences in the metaphysical, epistemological, and ethical beliefs that define how humans view, value, and interact with the natural world). Here, we present an exploratory measure of environmental worldview diversity among undergraduate students enrolled in natural resource‐related programs. We tested our procedure at Oregon State University, a large public land‐grant university in the United States. Many students reported metaphysical, epistemological, and/or ethical beliefs that deviate from what has been philosophically characterized as the dominant western worldview of natural resources (anthropocentric, dualistic, hierarchical, utilitarian, and mechanistic). Our results suggest that, although forestry students' environmental worldviews are in some ways more closely aligned with the dominant western worldview than other students in natural resources, generally student worldviews reflect a long‐term generational shift away from a strict resource‐commodity value orientation, as documented in the past research. Our findings highlight the importance of considering environmental worldviews as a dimension of diversity within the new generation of natural resource students. Future efforts toward understanding these levels of difference can be important assets in designing programs that appeal to a wide variety of students, ultimately helping efforts to recruit and retain a diverse pool of aspiring natural resource professionals. Abstract : Our results suggest that, although forestry students' environmental worldviews are in some ways more closely aligned with the dominant western worldview than other students in natural resources, generally their worldviews reflect long‐term generational shifts away from a strict resource‐commodity value orientation, as documented in past research. Our findings highlight the importance of considering environmental worldviews as a dimension of diversity within the new‐generation natural resource students. Future efforts toward understanding these levels of difference can be important assets in designing programs, which appeal to a wide variety of students, ultimately helping efforts to recruit and retain a diverse pool of aspiring natural resource professionals.